The Influence of Motivation and Job Satisfaction on Employee Performance in the Personnel and Human Resources Development Agency of North Musi Rawas Regency - Yunita, Welli; Halin, Hamid (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to determine the effect of motivation and job satisfaction on employee performance at BKPSDM Musi Rawas, South Sumatra. This study utilized primary data and secondary data. Data collection techniques utilized a questionnaire. Respondents in this study were 53 employees. The method of analysis in this study utilized multiple linear regression. The results show that motivation and job satisfaction simultaneously have a significant positive effect on employee performance. This research is expected to be useful for companies to improve employee performance through motivation and job satisfaction.